Analysis of the Health and Safety Behaviour of Domestic Tourists During Their Travels - Isni, Khoiriyah; Sofianingrum, Arnita; Purnamasari, Dwi Putri; Saidah, Ayu; Rifai, Muchamad; Agustin, Helfi (Universitas Airlangga, 2023)
Introduction: Indonesia's tourism continues to grow annually despite increasing competition in the sector. This study assesses the risk behavior of Indonesian domestic tourists in shopping areas in the Special Region of Yogyakarta, particularly in terms of health and safety. Methods: This quantitative research used a cross-sectional approach and was conducted in shopping areas in the Special Region of Yogyakarta. Using accidental sampling, 212 domestic tourists aged at least 17 years were selected as respondents. This study incorporated primary data that were collected from questionnaires asking about the characteristics of the respondents and their knowledge, attitudes, and behavior concerning healthy and safe travel, and was examined using univariate and bivariate analyses. Results: More than 70% of the respondents were female and teenagers (17-24 years old). Approximately 53% of the respondents had low education, but most had good knowledge, positive attitudes, and good behavior towards travel health and safety. Thus, gender (p-value= 0.000) and tourist attitudes (p-value = 0.000) were significantly associated with health and safety behaviors during travel. Conclusion: The findings show that domestic tourists have good knowledge of and positive attitudes towards travel health and safety risks.